Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) pada Pegawai Kantor Pemadam Kebakaran (Damkar) Kabupaten Batang Hari - Siswati, Etty; Fauzani, Evi; Kosasi, Niki; Khoiroh, Nadiatul; Realita, Dea (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to analyze the influence of job satisfaction and organizational commitment on organizational citizenship behavior (OCB) in Fire Department (Damkar) employees in Batang Hari Regency. The method used is quantitative descriptive using multiple linear regression analysis tools. The results of this research reveal that simultaneously and partially there is a significant influence between the variables of job satisfaction and organizational commitment on organizational citizenship behavior (OCB) in employees of the Fire Department (Damkar) in Batang Hari Regency.